Social Mobility and Democratic Attitudes: Evidence From Latin America and Sub-Saharan Africa. (September 2019) - Houle, Christian; Miller, Michael K.
How does intergenerational social mobility affect support for democracy? Although a large literature examines how personal income and inequality influence regime change and democratic attitudes, there has been little work on social mobility. We employ individual level data from the Afrobarometer and Latinobarometer, covering 33 democracies and nondemocracies, to provide the first analysis of how personal experiences of intergenerational mobility influence support for democracy. We find that mobility predicts democratic attitudes, even controlling for education and current economic situation. We also show that the effect does not run through preferences for redistribution. We instead propose two alternative mechanisms. First, individuals living in democracies credit (or blame) the regime when they experience mobility. Second, upward mobility transforms a range of values, such as personal autonomy and trust, that render individuals more supportive of democracy. Our results present a warning for democracies facing steadily declining social mobility, including the United States.